Thailand's halal gastrodiplomacy to Indonesia: A study from the glocalisation perspective - Utomo, Ario Bimo; Sari, Kendalita (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This article describes how globalisation paves a way toward Thailand's decision to develop its gastrodiplomacy strategy. In more detail, the practice that the author will examine is the practice of Thai gastrodiplomacy with Indonesia, which is directed explicitly to promoting their halal products. This research is descriptive and uses a case study approach, which may provide a deeper picture of a phenomenon in social sciences. Through the Thailand case study, we can see that so far, countries that have a comparative advantage in the culinary field can also respond to globalisation in their way. Responding to the high demand from the global trend of halal tourism, Thailand has slightly adjusted its gastrodiplomacy strategy towards the halal aspect. This also improves the image of those already popular with sex tourism. Uniquely, this halal gastrodiplomacy has also made them successful in gaining markets in other countries despite not being a Muslim-majority country. This research highlights that the practice of gastrodiplomacy can be viewed from various perspectives. One of them is the perspective of globalisation, which investigates how interactions between people can change our perception of objective and subjective needs and how linking these two needs creates new modes of activity.